2020
DOI: 10.3758/s13415-020-00834-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of theta-burst transcranial magnetic stimulation over the dorsolateral prefrontal cortex on emotion processing in healthy volunteers

Abstract: Repetitive transcranial magnetic stimulation is a potential treatment option for depression, with the newer intermittent theta-burst stimulation (iTBS) protocols providing brief intervention. However, their mechanism of action remains unclear. We investigated the hypothesis that iTBS influences brain circuits involved in emotion processing that are also affected by antidepressants. We predicted that iTBS would lead to changes in performance on emotion-processing tasks. We investigated the effects of intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 93 publications
(98 reference statements)
1
12
0
Order By: Relevance
“…Confirmatory behavioral analyses indicated that changes in amygdala reactivity were accompanied by a decrease in negative valence and an increase in positive valence ratings following multiple doses of iTBS, which may reflect changes in the salience attributed to affective stimuli. Together, these results parallel previous studies showing that left DLPFC stimulation improves emotion processing by inhibiting negative bias and improving affective processing of positive stimuli (14,2023).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Confirmatory behavioral analyses indicated that changes in amygdala reactivity were accompanied by a decrease in negative valence and an increase in positive valence ratings following multiple doses of iTBS, which may reflect changes in the salience attributed to affective stimuli. Together, these results parallel previous studies showing that left DLPFC stimulation improves emotion processing by inhibiting negative bias and improving affective processing of positive stimuli (14,2023).…”
Section: Discussionsupporting
confidence: 90%
“…Targeting the left dorsolateral prefrontal cortex (DLPFC) via excitatory rTMS and iTBS has been shown to improve emotion processing in both healthy and patient populations, by inhibiting negative bias and increasing response for positive stimuli (20)(21)(22), while right-sided prefrontal stimulation is associated with increased right amygdala activation and enhanced attentional allocation to threatening stimuli (23,24). Furthermore, it has been reported that left prefrontal iTBS also decreases functional connectivity between DLPFC and limbic regions (25,26), which is increased in individuals with FMD (8).…”
Section: Introductionmentioning
confidence: 99%
“…If the pattern of stimulation is intermittent (iTBS), i.e., short trains of 2 s given every 10 s, cortical excitability is enhanced and MEP amplitude increases up to 30 min after stimulation (LTP-like effects). If the pattern is continuous (cTBS), i.e., bursts given continuously for 40 s, cortical excitability is inhibited and MEP amplitude decreases for 20–60 min (LTD-like effects) [ 155 , 163 , 164 , 165 , 166 ].…”
Section: Neurophysiological Changes In Plasticity and Metaplasticimentioning
confidence: 99%
“…Since Coan and Allen pointed out that activity in the alpha range is inversely related to the underlying cortical processing [ 30 ], the authors suggested that cTBS increases brain activity for positive stimuli. More recently, several studies investigated the effects of one or two iTBS sessions on mood and/or emotion processing in healthy volunteers with parameters commonly used when treating mood disorders [ 23 , 31 , 32 , 33 , 34 ], which usually favor iTBS over the left DLPFC ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Harmer et al, antidepressant treatments may be underlaid by a rapid change in emotion processing that then leads to a slower improvement in mood [ 35 ]. The antidepressant effect of iTBS may result from emotion processing changes [ 33 ]. Assuming that the therapeutic mechanism of iTBS shares the same mechanism in healthy subjects, we suggest that repeated iTBS sessions over the left DLPFC over several days could modulate brain activity during emotion processing.…”
Section: Introductionmentioning
confidence: 99%